AC Losses in YBCO-Added Bi1.6Pb0.4Sr2Ca2Cu3O δ Superconductors - A. Arlina; S.A. Halim; M.M. Awang Kechik; S.K. Chen (2015)
The effect of YBCO adding on the superconducting of BPSCCO system with nominal starting composition of (Bi1.6Pb0.4Sr2Ca2Cu3O δ )1−x(YBCO) x with x = 0.00−0.10 was studied. The preparation methods used to prepare the samples are the conventional solid-state techniques. From the XRD data, it is observed that the percentage of the Bi-2223 phase increases and Bi-2212 decreases for addition x = 0.02–0.04, respectively. The effect of YBCO addition on the BPSCCO system also has been investigated in term of AC susceptibility study. We have studied the various applied field dependence of the AC susceptibility in polycrystalline samples. The AC susceptibility measurements in the range 0.05 to 2.00 Oe show that as the applied fields increases, the intergranular AC loss peaks move to lower temperature, and also height decreases and width increases. The effect of YBCO addition for the intergranular critical current J cm, and the presence of weak links that coupled the superconducting grains were defined.